BALANCE TWELVE EXERCISE WITH HATHA YOGA MAXIMIZES DYNAMIC BALANCE AND LOWERS ELDERLY ANXIETY - Asita Rohmah Mutnawasitoh; Dea Linia Romadhoni (P3M Universitas 'Aisyiyah Surakarta, 2023)
The elderly experience physiological changes that cause balance and anxiety disorders, it is important to provide a combination exercise program that can maximize balance while reducing anxiety. The purpose of the study was to find out that the combination of balance twelve exercises with hatha yoga can maximize dynamic balance and reduce anxiety in the elderly. Experimental research, with pretest and posttest control group design. The research sample amounted to 28 pre-elderly who were selected based on inclusion and exclusion criteria. Divided into Group 1 is given hatha yoga, and Group 2 is given a combination of balance twelve exercises with hatha yoga. Training for 6 weeks with a frequency of 3 times a week. Measurement of balance with the Berg balance scale, and measurement of anxiety with the Hamilton anxiety rating scale. The results of the balance value of Group 2 p> 0.000 with a mean difference and a percentage increase of 6.86±0.663 (15.50 %). for anxiety, the results were p> 0.001 with a mean difference and a decreasing percentage of 4.64±1.82 (50.76%). In the balance of Group 1, the results were p>0.000 with a mean difference and a percentage increase of 4.50±0.519 (10.51%) for anxiety, the results were p>0.000 with a mean difference and a percentage decrease of 1.85±0.363 (20.08%). It can be concluded that the combination of balance twelve exercises with hatha yoga maximizes dynamic balance and reduces anxiety.